Effect of Wet Salting Method on the Characteristic of Salted Snakedhead Fish (Ophiocepalus striatus) - Rahmani, Rahmani; Yunianta, Yunianta; Martati, Erryana (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Dried and salted snakehead fish is a product that processed by salting and drying. Fish salting depends on salt concentration and salting duration. The aim of the research was to know the effect of salt concentration and salting duration on physical, chemical, and organoleptic characteristics of salted snakehead fish.The research used Randomized Block Design (RBD), which consisted of two factors. The first factor was salt concentration that consisted of three levels: 20%, 30% and 40% (w/v). Second factor was salting time that consisted of three levels: 12, 24 and 34 hours. Data was analyzed by variance analysis (ANOVA) and followed by LSD or DMRT test (α=5%). The best treatment was selected by De Garmo method supported by t-test to compare best treated sample to commercial salted snakehead.The results showed that salt concentration and salting duration has no significant effect (α=5%) on chemical parameters, including protein content, salt content, water content, ash content, TVB value and water activity (AW). However, organoleptic parameters showed significant effect (α=5%) on hedonic scale of taste. The interaction of both treatments had no significant effect on all parameters.Based on the results, the best treatment was obtained at the application of 20% salt concentration and 24 hours salting time, which had physicochemical parameters as follow: 52,74% protein content, 7,93% salt content, 24,02% water content, 0,19% ash content, 12,74 mg N/100 g TVB value and 0,73 Aw. The results of the microbiological analysis showed that salted snakehead fish that stored for 30 days contained total fungi of 1,9X104 colony/ml, and also total halophilic bacteria of 2,9X105 colony/ml.Keywords: salt concentration, salting duration, salted snakehead fish